Free‐breathing simultaneous myocardial T1 and T2 mapping with whole left ventricle coverage. Issue 3 (20th October 2020) - Guo, Rui; Cai, Xiaoying; Kucukseymen, Selcuk; Rodriguez, Jennifer; Paskavitz, Amanda; Pierce, Patrick; Goddu, Beth; Thompson, Richard B.; Nezafat, Reza
Abstract : Purpose: To develop a free‐breathing sequence, that is, Multislice Joint T1 ‐T2, for simultaneous measurement of myocardial T1 and T2 for multiple slices to achieve whole left‐ventricular coverage. Methods: Multislice Joint T1 ‐T2 adopts slice‐interleaved acquisition to collect 10 single‐shot electrocardiogram‐triggered images for each slice prepared by saturation and T2 preparation to simultaneously estimate myocardial T1 and T2 and achieve whole left‐ventricular coverage. Prospective slice‐tracking using a respiratory navigator and retrospective image registration are used to reduce through‐plane and in‐plane motion, respectively. Multislice Joint T1 ‐T2 was validated through numerical simulations and phantom and in vivo experiments, and compared with saturation‐recovery single‐shot acquisition and T2 ‐prepared balanced Steady‐State Free Precession (T2 ‐prep SSFP) sequences. Results: Phantom T1 and T2 from Multislice Joint T1 ‐T2 had good accuracy and precision, and were insensitive to heart rate. Multislice Joint T1 ‐T2 yielded T1 and T2 maps of nine left‐ventricular slices in 1.4 minutes. The mean left‐ventricular T1 difference between saturation‐recovery single‐shot acquisition and Multislice Joint T1 ‐T2 across healthy subjects and patients was 191 ms (1564 ± 60 ms versus 1373 ± 50 ms; P < .05) and 111 ms (1535 ± 49 ms vs 1423 ± 49 ms; P < .05), respectively. The mean difference in left‐ventricular T2 between T2 ‐prep SSFP and Multislice Joint T1 ‐T2 across healthy subjects and patients was −6.3 ms (42.4 ± 1.4 ms vs 48.7 ± 2.5; P < .05) and −5.7 ms (41.6 ± 2.5 ms vs 47.3 ± 2.7; P < .05), respectively. Conclusion: Multislice Joint T1 ‐T2 enables quantification of whole left‐ventricular T1 and T2 during free breathing within a clinically feasible scan time of less than 2 minutes.